2007
DOI: 10.1016/j.bcp.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of methionine oxidation of hERG potassium channels

Abstract: Reactive species oxidatively modify numerous proteins including ion channels. Oxidative sensitivity of ion channels is often conferred by amino acids containing sulfur atoms, such as cysteine and methionine. Functional consequences of oxidative modification of methionine in hERG1 (human ether à go-go related gene 1), which encodes cardiac I Kr channels, are unknown. Here we used chloramine-T (ChT), which preferentially oxidizes methionine, to examine the functional consequences of methionine oxidation of hERG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…This observation may be consistent with posttranslational modulation of hERG channel function. In fact, oxidative modulation of hERG channels has been recently reported to alter I Kr (45).…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be consistent with posttranslational modulation of hERG channel function. In fact, oxidative modulation of hERG channels has been recently reported to alter I Kr (45).…”
Section: Discussionmentioning
confidence: 99%
“…(55). Yet another study found that the hERG K + channel could be inactivated by Met oxidation by chloramine-T in HEK293 cells and that this process could be attenuated by MsrA, suggesting the importance of reversible Met oxidation and reduction in the control of hERG K + channel function (63). It has also been suggested that regulation of Met oxidation in a protein involved in calcium flux may play an important role in regulating energy metabolism and adaptation to oxidative stress (3).…”
Section: Fig 3 Selenocysteine-containing Msrb1mentioning
confidence: 99%
“…The activation was slowed during depolarization to 30 mV but accelerated during depolarization to 0 or -10 mV and the deactivation was also accelerated upon repolarization. In the presence of recombinant bovine MsrA a diminished effect of ChT was observed (123). The result indicated that methionine oxidation is at least partially responsible for the Kv11.1 current inhibition.…”
Section: Sahoo Et Almentioning
confidence: 84%
“…Su et al (123) have shown that ChT, which preferentially oxidizes methionine, significantly decreased Kv11.1 current. The activation was slowed during depolarization to 30 mV but accelerated during depolarization to 0 or -10 mV and the deactivation was also accelerated upon repolarization.…”
Section: Sahoo Et Almentioning
confidence: 98%